Effect of surface charge and other critical parameters on the adsorption of dyes on SLS coated ZnO nanoparticles and optimization using response surface methodology. Issue 4 (August 2020) - Pinheiro, Dephan; Sunaja Devi, K.R.; Jose, Ajay; Rajiv Bharadwaj, N.; Thomas, K.J.
Graphical abstract: Highlights: Highly effective SLS modified ZnO adsorbent prepared by electrochemical method. SLS coated ZnO nanoparticles studied for charge specific adsorption of organic dyes. The catalyst is effective for the removal of cationic dyes. Adsorption process follows pseudo second order kinetics and Langmuir isotherm. Adsorption is spontaneous, endothermic and chemical in nature. Abstract: Adsorption is a possible method with distinct advantages to remediate pollution due to dyes. Sodium Lauryl Sulfate (SLS) coated ZnO nanoparticles were synthesized using the electrochemical method. The final product was dried at different temperatures, 60, 120, 150 and 300 °C. The sample dried at 60 °C was found to have the maximum SLS coating on its surface providing high negative charge density. This facilitates the adsorption of cationic dyes on its surface through electrostatic attraction. The effect of SLS on the adsorption process was confirmed by comparing it with ZnO without SLS. The effect of important parameters such as amount of adsorbent, concentration of dye, temperature and time on the percentage of adsorption was investigated using Box-Behnken design (BBD) of Response Surface Methodology (RSM). The prepared catalysts were characterized using X-ray diffraction analysis, infrared spectroscopic analysis, scanning electron microscopy, elemental detection analysis, thermogravimetric and zeta potential analysis. Finally, the study was extended to Langmuir and Freundlich isotherms in order to confirm the type of adsorption. The adsorption kinetics studies showed that it obeys pseudo second order kinetics.